1985
DOI: 10.1111/j.1365-2109.1985.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Oreochromis mossambicus (Peters) eggs against commonly occurring potentially pathogenic bacteria and fungi under artificial hatchery conditions

Abstract: Abstract. There is an increasing potential for artificial incubation of tilapia eggs. Hatchability observed in artificial systems is less than 62%. Four chemicals generally used as disinfectants for the fish eggs were tested in a controlled experiment together with ultraviolet irradiation of the water. A range of dose levels was tested for each chemical and is compared and assessed in terms of improved hatching rates. Effective disinfection improved the hatchability of eggs above 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 10 publications
(17 reference statements)
2
18
0
Order By: Relevance
“…were also reported in Mozambique tilapia (O. mossambicus) eggs from the artificial incubation systems (Subasinghe and Sommerville 1985). In our study, A. hydrophila was the most frequently found isolate.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…were also reported in Mozambique tilapia (O. mossambicus) eggs from the artificial incubation systems (Subasinghe and Sommerville 1985). In our study, A. hydrophila was the most frequently found isolate.…”
Section: Discussionsupporting
confidence: 49%
“…Treasurer et al (2005) reported the number of 3100 to 38 000 CFU/ml of egg in cod and haddock, while the colony counts in California yellowtail, white seabass, and California halibut were 16.7, 110.0, and 233.3 CFU/ml of egg, respectively (Stuart et al 2010). In our study, the bacterial counts (1.57 × 10 3 CFU/ml) in the hatchery water were comparable to those in the rearing system of California halibut (10 4 CFU/ml) (Stuart et al 2010) and of Mozambique tilapia (6.25 × 10 3 CFU/ml) (Subasinghe and Sommerville 1985). The relatively high numbers of bacteria colonized on the surface of Nile tilapia eggs may be attributed to the rapid growth of the waterborne pathogens in temperate water temperature, particularly in the hatchery facility that is in the tropical region as Thailand, and the gelatinous matrix surrounding the eggs may be an appropriate substrate for bacterial proliferation.…”
Section: Discussionmentioning
confidence: 49%
“…In vitro studies have shown that a 5 min treatment with 25 mg active iodine 1-l is effective against several fish pathogens (Amend and Pie&h, 1972;Ross and Smith, 1972) and lO-15min treatments with 50-100 mg active iodine 1-l have been recommended for surface disinfection of fis,h eggs from many freshwater species (McFadden, 1969;Amend, 1974;Schachte, 1979;Subasinghe and Sommerville, 1985). Positive effects in seawater of treating Atlantic halibut eggs for 10 min with 50 mg active iodine 1-l have also been reported (Bergh et al, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…At higher doses of Buffodine the bactericidal effect was better, but these doses did not have a good safety margin to lethal doses. Toxic effects have previously been observed after 10-15 min treatments with 2 200 mg active iodine 1-l (McFadden, 1969;Wright and Snow, 1975;Subasinghe and Sommerville, 1985). The toxicity of iodophores is pH dependent, i.e.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation